Le tribunal d’opinion de Tôkyô pour les « femmes de réconfort » - Rumiko Nishino (Droit et Cultures, 2009)
Since the 1930s, Japan had organized the kidnapping and mass deportation of young Asian women into military brothels campaign in the occupied territories. Although the facts were known at the time of the Tokyo trial (the International Military Tribunal for the Far East), and trials of BC war criminals, sexual violence against women were not recognized as full war crimes, and the whole story remained was largely ignored until the coming out of Korean victims in the 1990s. Following the mobilization by those women from Korea and other Asian countries, an opinion court was held in Tokyo in December 2000, at the initiative of VAWW-NET (Violence against Women in War Network). The goal was to indict those responsible and to consider remedial measures. The article presents the meaning of the court and examines further perspectives.